Pengembangan Nature School melalui Pelatihan Media Pembelajaran Digital di YAKASE Jombang - Rahmania Sri Untari; Fitria Nur Hasanah; Mochamad Rizal Yulianto; Rakhmat Auliya Hidayat; Muhammad Irfan Jazuli (Belantika Pendidikan, 2022)
Covid 19 pandemic is still not over in this time. It makes anxiety for the world of education, especially for school and society. It can be seen that the phenomenon of unready school and society condition to face the variety changes in learning habits. Yakase nature school is built for the unrest of the souls due to the shackles of the world system. Learning media has an important role to increase students’ interest in learning, especially in lower grades. It can be proved that lower grade students are not able to think abstractly, so the material taught by nature school assistants needs to be visualized in a more real/concrete form. Digital learning media training activities aim to increase and develop the ability of companions in using computers. By making interesting animations, the students are not bored and also have special skills in the field of technology. The results of this training activity are expected to help stimulate companion technology skills in creating digital learning media.Masih belum jelas masa berakhir pandemic covid-19 menimbulkan kecemasan bagi dunia pendidikan, terutama jika melihat fenomena kondisi masyarakat dan sekolah yang belum siap menghadapi kejutan perubahan kebiasaan pembelajaran. Sekolah alam YAKASE didirikan karena keresahan jiwa-jiwa akibat belenggu sistem dunia. Media pembelajaran mempunyai peran penting untuk meningkatkan minat belajar siswa, khususnya di kelas rendah, karena siswa kelas rendah belum mampu berpikir abstrak, sehingga materi yang diajarkan oleh pendamping sekolah alam perlu divisualisasikan dalam bentuk yang lebih nyata/kongkrit. Kegiatan pelatihan media pembelajaran digital bertujuan untuk menambah dan mengasah kemampuan pendamping dalam menggunakan komputer, yaitu membuat animasi yang menarik, sehingga siswa-siswi tidak bosen dan juga memiliki keterampilan khusus di bidang teknologi. Hasil kegiatan pelatihan ini diharapkan dapat membantu stimulasi keterampilan teknologi pendamping dalam membuat media pembelajaran digital